2016
DOI: 10.1039/c6ra04207d
|View full text |Cite
|
Sign up to set email alerts
|

Chemical components from the seeds of Catalpa bungei and their inhibitions of soluble epoxide hydrolase, cholinesterase and nuclear factor kappa B activities

Abstract: Two new chlorinated iridoids, named bungosides A (1) and B (2), were isolated from the seeds of Catalpa bungei (family Bignoniaceae). Their structures were elucidated on the basis of NMR analysis. Twenty known compounds (3-22) were also characterized, including in one case (6-O-phydroxybenzoylglutinoside, 3) the assignment of the absolute configuration by employing electronic circular dichroism (CD) and time-dependent density functional theory (TDDFT) calculations. Compounds 1-3 were unusual cage-like iridoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…In this study is the first report of sEH inhibitory activity of compounds 6 , 7 , 9 and 10 . Compounds 1 , 3 and 8 have previously shown significant sEH inhibitory activity related to cardiovascular disease [ 30 , 31 , 32 ]. These sEH results showed that the phenylpropanoid derivatives exhibited stronger inhibitory activity than the triterpene compounds.…”
Section: Resultsmentioning
confidence: 99%
“…In this study is the first report of sEH inhibitory activity of compounds 6 , 7 , 9 and 10 . Compounds 1 , 3 and 8 have previously shown significant sEH inhibitory activity related to cardiovascular disease [ 30 , 31 , 32 ]. These sEH results showed that the phenylpropanoid derivatives exhibited stronger inhibitory activity than the triterpene compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic compounds reported in literature as owners of anticholinesterase activity are p -coumaric acid ( p -Cou) and luteolin (Lut) [ 14 , 16 ] in addition to lignans isolated from plants such as syringaresinol (Syr) (which showed an inhibitory effect against AChE) [ 15 ], and pinoresinol (Pin) (which displayed selective inhibitory effects on BuChE, but not against AChE) [ 17 ]. The content of these compounds were higher in ′Brava′ than in ′Mansa′ olive oils, as mentioned before.…”
Section: Discussionmentioning
confidence: 99%
“…Some phenolic compounds have already addressed to exhibit several remarkable biological activities on inhibition of the previously described enzymes: p -coumaric acid, luteolin and lignans including pinoresinol and syringaresinol as owners of anticholinesterase activities [ 14 , 15 , 16 , 17 ]; oleocanthal, hydroxytyrosol, p -coumaric acid, and luteolin with inhibitory activity against 5-LOX [ 18 , 19 , 20 ] and flavonoids including apigenin and luteolin as responsible of the inhibition of h- MAOs [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The residue was dissolved in pyridine (0.5 mL), to which l -cysteine methyl ester hydrochloride in pyridine (0.1 M, 0.5 mL) was added. After reacting at 60 °C for 1 h, trimethylsilylimidazole (0.05 mL) was added to the reaction mixture and kept at 4 °C for another 8 h. The mixture was analyzed by GC-MS. By comparison of the retention time of the authentic sample, the monosaccharide of compound 1a was determined to be d -fucose ( t R = 21.040 min) . Other compounds were treated under the same conditions.…”
Section: Experimental Sectionmentioning
confidence: 99%